Caring perawat dan tingkat kecemasan pada pasien preoperasi: studi korelasi - Agnes Erida Wijayanti; Tiara Liatika (Health Sciences and Pharmacy Journal, 2019)
Caring for nurses in the form of nursing services applied in providing nursing care. Which one of them on psychological aspects including anxiety. The objective of this study is to know the relation caring nurse’s with anxiety level in preoperating patients in inpatient room Hospital Regional Public Wonosari Yogyakarta. This study used an observational analytic design using cross-sectional. Sampling used accidental sampling, with 83 respondents. Data analysis using Spearman Rank test with significance level p = 0,05 or α = 5%. Anxiety instruments using Hospital Anxiety and Depression Scale (HADS). The result of this studi showed that a total of 61,5% of nurse, nurses with good category, 34,9% nurse, nurses with enough category, and 3,6% caring nurses with less category. 57,8% of the anxiety category was light, 32,5% was in medium category, and 9.6% were in the weight category. As for the correlation results, it was obtained p value 0,0021 (p 0,05), The strength of the relationship was 0,021-0,253. Conclusion of this study was there was a relation caring nurse’s with anxiety level in preoperating patients in inpatient room Hospital Regional Public Wonosari Yogyakarta.